The Experiment of Partial Discharge for Cast Resin Transformer - Aiamrungruang, Phitthaya; Pannil, Pittaya; Dorkmai, Kritsada; Maneerot, Sakda; Jeenmuang, Siwakorn; Pattanadech, Norasage (My University, 2024)
Dry-type cast resin transformers, utilizing epoxy resin insulation instead of traditional liquid insulation like mineral oil, are designed to prioritize safety, avoid fire hazards, be environmentally compatible, and endure short circuits well. Limitations of dry-type transformers are the installation area by which it should be dry, free from dust, excessive moisture, fertilizers, chemicals, and other corrosive fumes or fumes. This paper investigates the Partial Discharge (PD) phenomena occurring on a 12 kV dry-type transformer surface using HighFrequency Current Transformers (HFCT) with 100 kHz -20 MHz bandwidth as a PD detection device. The simulated PD sources were made from the conductive wire. Moreover, the scheme of winding connections in the dry-type transformer related to cross-talk phenomena between transformer coils is also reported. The recorded Phase-resolved PD (PRPD) and the PD Inception Voltage (PDIV) have been summarized and compared, as described in this paper.
Keywords: dry-type transformer; HFCT; partial discharge; PDIV; PRPD